Multidetection of antibiotics in liver tissue by Ultra-High-Pressure-Liquid-Chromatography tandem Mass Spectrometry - Freitas, Andreia (2014)
A multiresidue quantitative screening method covering 39 antibiotics from 7 different families by Ultra-High-Pressure-Liquid-Chromatography tandem Mass Spectrometry (UHPLC-MS/MS) is described. Sulfonamides, trimethoprim, tetracyclines, macrolides, quinolones, penicillins and chloramphenicol are simultaneously detected in liver tissue. A simple sample treatment method consisting of extraction with a mixture of acetonitrile and ethylenediaminetetraacetic acid (EDTA) followed by solid-phase extraction (SPE) with a hydrophilic-lipophilic balanced (HLB) cartridge was developed. The methodology was validated, in accordance with Decision 2002/657/EC, by evaluating the following required parameters: decision limit (CCα), detection capability (CCβ), specificity, repeatability and reproducibility. The precision, in terms of the relative standard deviation, was under 22% for all of the compounds, and the recoveries were between 80% and 110%. The CCα and CCβ were determined according to the maximum residue limit (MRL) or the minimum required performance limit (MRPL), when established.